The Brunei Bay as an Effluent Receiving Waterbody: Observations during the Start-up Period of a Kraft Pulp and Paper Mill - Mohamed, Murtedza; Chin, L. L.; Lim, T. S. (1990)
The water quality of Brunei Bay, Malaysia, subsequent to receiving iffluent from a pulp and paper mill, was monitored. Conventional water quality parameters such as dissolved oxygen, suspended solids, and biochemical oxygen demand were used as indicators to compare the present status of the bay water quality with that of the baseline. Generally, data gathered during the first 16 months of the mill operation did not indicate marked changes in the bay water quality. Levels of suspended solids, total organic carbons, and 1, 1-dichlorodimethyl sulfone in the bay water were used as indicators in the determination of dispersion pattern of the effluent in the coastal areas of the bay.